EVALUATION OF THE FIRST NATIONAL PROGRAM FOR RARE DISEASES IN SERBIA (2020-2022): RESULTS AND EXPECTATIONS - Arsić, Jasmina; Stojiljković, Dragana; Stojkov, Svetlana (Archives of Pharmacy, 2023)
Rare diseases (RD) are an important public health priority of Health Policies at the national, European, and global level. The specificity of the problems by RD patients in Serbia is reflected in a series of inequalities or inaccessibility of the right to health and social care. On the initiative of the Ministry of Health of the RS and the National Organization for Rare Diseases in the RS, the first National Program for Rare Diseases for the period 2020-2022 was adopted (1). The general goal of the Program is: the improvement of health care and quality of life of RB patients; and the specific goals are: 1) improvement of prevention and diagnosis of RD; 2) improved treatment, care, and social support of RD patients. The evaluation of Program (2) showed that: the general goal was not achieved, because no survey was conducted on the degree of satisfaction of RD patients. The evaluation of the special objective 1 showed that there is a need for better recording of the number of people with suspected RD. The evaluation of special objective 2 showed a partial realization with the need for changes in certain legal regulations in the field of drugs, biological material, and indicators on the number of days for which therapy is available. The evaluation of the first National Program for the treatment of RD in Serbia showed that better cooperation between institutions and patient associations is necessary in order to encourage progress in realizing the rights of RD patients.